2021
DOI: 10.1136/bjsports-2020-103757
|View full text |Cite|
|
Sign up to set email alerts
|

Body checking in non-elite adolescent ice hockey leagues: it is never too late for policy change aiming to protect the health of adolescents

Abstract: ObjectivesThe objective of this study is to evaluate the effect of policy change disallowing body checking in adolescent ice hockey leagues (ages 15–17) on reducing rates of injury and concussion.MethodsThis is a prospective cohort study. Players 15–17 years-old were recruited from teams in non-elite divisions of play (lower 40%–70% by division of play depending on year and city of play in leagues where policy permits or prohibit body checking in Alberta and British Columbia, Canada (2015–18). A validated inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…This suggests that greater bodychecking experience does not protect adolescent ice hockey players from injury or concussion, and that the policy change to disallow bodychecking had no unintended consequences with regard to injury in subsequent years. In addition to the strong evidence showing reduced rates of injury in evaluations of the policy change, 4 , 9 , 10 our results provide further evidence in support of removing bodychecking in youth ice hockey to prevent injury. Although the effect of bodychecking experience has not been previously explored among 15- to 17-year-old players, previous research among 13- and 14-year-old players found similar rates of injury and concussion among those who had 2 years of bodychecking experience and those who had none.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This suggests that greater bodychecking experience does not protect adolescent ice hockey players from injury or concussion, and that the policy change to disallow bodychecking had no unintended consequences with regard to injury in subsequent years. In addition to the strong evidence showing reduced rates of injury in evaluations of the policy change, 4 , 9 , 10 our results provide further evidence in support of removing bodychecking in youth ice hockey to prevent injury. Although the effect of bodychecking experience has not been previously explored among 15- to 17-year-old players, previous research among 13- and 14-year-old players found similar rates of injury and concussion among those who had 2 years of bodychecking experience and those who had none.…”
Section: Discussionsupporting
confidence: 66%
“… 5 8 These policy changes have been associated with reduced rates of injury, including concussion. 4 , 9 , 10 Despite this strong evidence, some argue that gaining experience in bodychecking earlier may protect players from injuries, including concussions, when they play in the older age categories where bodychecking is allowed. 11 A previous prospective cohort study of 13- and 14-year-old players found similar rates of overall injury and concussion among those with 2 years of experience with bodychecking and those with none.…”
mentioning
confidence: 99%
“…In evaluation of these policy changes, disallowing body checking in games was associated with a 50% and 64% reduction in the rate of all injury and concussion in U-13 players, respectively 14. Reduced injury rates have also been found in the non-elite U-15 and U-18 (ages 15–17 years; formerly called Midget) age categories 15 16. It is critical, however, to inform national and regional ice hockey associations regarding a greater understanding of any unintended consequences of such policy change.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies were valuable for injury prevention purposes because they provided evidence for the value of raising the permitted age for bodychecking to age 13–14-year-old players, 26 but none of these had long-term data for PCS due to bodychecking. Emery et al 27 studied 15–17-year-old hockey players in bodychecking versus non-bodychecking leagues in three cities in Canada and showed a much lower incidence of concussions in non-bodychecking cities, but there was no long-term follow-up recovery data.…”
Section: Discussionmentioning
confidence: 99%